The effect of practicing with a reduced diameter RIM on the efficiency of free throws with young basketball players - Erculj, F.; Trafela, A.; Strumbel, E.; Jakovljevic S.; Mandic, R. (Kinesiologia Slovenica, 2020)
Even though free throws account for approximately 20% of all points in a basketball game, practicing free throws is often not given enough attention. We analyse the efficiency of practicing free throws with a reduced diameter rim to monitor the changes of successful free throws and the changes of the angle of ball entry. Our sample included 57 top young basketball players, aged 15 to 18. After the experimental programme of practicing free throws, the efficiency of the free throws did not increase (neither during testing nor during competition) and neither did the angle of ball entry. The angle of entry with a standard and a reduced diameter rim are strongly correlated (r = 0.86) - most players retain their own shooting trajectory, regardless of the diameter of the rim. It seems that using a reduced diameter rim by itself, without instruction, does not lead to an increase of the angle of entry.